The error of a quasi-static approach in predicting fluid forces on the hand in unsteady conditions - Kudo, S.; Wislon, B.; Takagi, H. (Japanese Journal of Sciences in Swimming and Water Exercise, 2007)
This study found that the quasi-static approach, which has been a major method for predicting the hand force in swimming since 1970s, led to errors in predicting the fluid forces acting on the hand in unsteady conditions. For examining unsteady flow conditions, the hand model was rotated in the flowing or non-flowing flume, and the fluid forces acting on the hand model and the dynamic pressure on the surface of the hand model were measured. The fluid forces were decomposed into the tangential (y-axis) and radial directions of rotation (z-axis), and the direction normal to the rotation plane (x-axis). The values of the dynamic pressure on the hand model showed the possibility of the generation of large vortices. The errors in predicting the fluid forces on the hand model just after the model rotation are likely to be due to the effects of the large vortices generated by the accelerating hand.